Kinetic Modeling of Mass Loss during Carbonization of Sodium Carboxymethyl Cellulose (CMC) Aerogels - Shapiee, Norrlaili (Annals of Mathematics and Physics, 2024)
The carbonization of sodium carboxymethyl cellulose (CMC) aerogels involves complex thermal decomposition processes leading to the formation of carbonaceous residues. Understanding the kinetics of mass loss during carbonization is vital for optimizing the production of CMC carbon aerogels with desired properties. In this study, a mathematical model is presented that describes the kinetics of mass loss during the carbonization process of CMC aerogels. This model considers the temperature and concentration dependence of CMC decomposition reactions and is validated against experimental data obtained at various conditions. The proposed kinetic model elucidates the underlying mechanisms governing mass loss during carbonization, offering valuable insights for the design and optimization of CMC carbon aerogels across diverse applications. Furthermore, the analysis of the experimental data reveals variations in both the reaction order and the rate constant for different concentrations of CMC aerogels, indicating distinct kinetic behavior. These findings contribute to a deeper understanding of the carbonization process and pave the way for tailored synthesis approaches to meet specific application requirements.